Educating Ulama to Address Climate Change: The Greenpeace MENA-Ummah for Earth - Rohayati, Tati (Studia Islamika, 2024)
To address the question of how extensively Islamic institutions have integrated climate change and environmental (CCE) issues into their curriculum, the Center for the Study of Islam and Society (PPIM) at UIN Jakarta, in collaboration with Greenpeace Middle East and North Africa (MENA) and Ummah for Earth, launched the Greenpeace MENA-Ummah for Earth program. This initiative, which began in July 2023, aims to analyze the curricula of Islamic universities and develop strategies for addresing climate and environmental principles into teaching materials. The program seeks to strengthen the role of Muslim community, particularly the Ulama, in promoting environmental conservation efforts.